Empirical Innovation Co. / Nur Zalikha Mohd Shahbuddin … [et al.] - Mohd Shahbuddin, Nur Zalikha; Roslan, Nur Natasya Syuhada; Abdul Shukor, Nurien Amyrah; Zakaria, Nur Afiqah; Zuber, Nur Nadiah (2022)
Our business, Empirical Innovation co. is located at No. 25 Jalan 1/27D, Seksyen 10, Subang Jaya. Our company, Empirical Innovation co. is run on a partnership business which consists of five members. Our business consists of a person who holds a position of general manager, financial manager, operational manager, marketing manager and organizational manager. In this business plan, we provide an organizational plan, marketing plan, financial plan, and operational plan for our use of targeted customers. Our product is a dryer hanger. We are inspired to do this product because it is a rare high technology product and it is not well known in Malaysia, however we believe that this will be a great opportunity to market this product in Malaysia. We are targeting people who have a problem with the limited laundry drying space and are busy with work. This also can help to lessen the burden of people doing their chores, by hanging their clothes at home when the rainy season is coming. Our mission is “we strive to give our customer satisfaction in home furnishing products at affordable prices as they are going their daily life” as our main importance is our customer satisfaction towards the product. As we know, customer satisfaction is one of the keys for any business to grow well and achieve a good reputation for our company. Our product is easy to use, and this will help our customer solve their problem. This also will improve their “everyday life”. The price is very reasonable and affordable as everyone will have a chance to buy it. Empirical Innovation co. launch the dryer hanger on the online platform to ensure people can recognize their product quickly since people nowadays spend their time surfing the internet. Our product, dryer hanger, can also be found at the supermarket such as Pacific and Lotus if they want to see it physically. As for now, Empirical Innovation co. is the only local company that produces dryer hangers in Malaysia. Our product capital starts from RM 500 000. All the partners contribute equally for RM 100 000 since we already conspired to build this business together. We face losses for our business in the first year of launching but growth in the next 2 years. We are sure that our business will have the potential for market growth and hope that it will be well-known not only in Malaysia but internationally.